The importance of and potential for stump treatment in Russian Karelia - Trishkin, Maxim (SLU/Southern Swedish Forest Research Centre, 2008)
The main goal of the work was detailed investigation in Republic of Karelia, which included literature observation, field study, laboratory analysis and interviewing in order to be able to suggest about possible market concerning stump treatments and its applying in perpetual perspective. Literature observation included information concerning the current situation with tree species composition, age structure of the forests and silviculture regimes. The field work was done on harvested areas for detailed investigation Norway spruce (Picea abies) stumps were taken, totally 22 clear cuttings were examined with 1430 of visually observed stumps and 220 samples from the stumps were taken for laboratory analyses (10 samples per harvesting area). The survey was made among 3 groups of respondents (forestry enterprises, scientists and forest industry) to find out the actual problems concerning new forest legislation, forest certification, about general health problems and regarding the Heterobasidion spp., as main species, which causing butt and root rot. Interviewing the logging companies was done in order to apply automated stump treatment. Field work shows that 36,4% from the totally visually observed stumps were rotten, although laboratory analysis shows that 6% from the total number of observed stumps were infected by Heterobasidion spp.. The results on survey demonstrate that real wood losses in forests between 3-5%. The proportion from total harvested volume of mechanized and manual harvesting both in thinning and in final felling were 59/41 and 13/87 percent respectively. The proportion of seasonal harvesting is shown that 54% of all operations are carried in winter time and 46% in summer time. Thus, Karelia has high technical potential of automate stump treatments, in spite of that situation with new Forest Legislation still unclear for forestry specialists, in term of responsibilities of main stakeholders. There are possibilities to gain stump treatments, but applying into the practical forestry can be done in two ways: by forcing from the governmental level, what was not done yet; by subsidizing of forest leasers to apply stump treatments after logging operations. Possible stump treatments are inhibited by the complex of factors and main are: financial and political.